The Effect of Personality Traits on Organizational Commitment: Moderating Role of Distributive Justice: A Case of Public Sector Female Colleges of District Peshawar - IMRAN SAEED; GHAYYUR QADIR; GHAYYUR QADIR (Journal of Business & Tourism, 2021)
Many studies have been conducted on personality traits in different organizations and an in different culture, different region and in different countries. The current study is talk about the two traits of personality i.e agreeableness and neuroticism and their effect on employee organizational commitment. And the main contribution of this study is to introduce distributive justice as a moderator variable. Data was collected from public sector female colleges of a Peshawar district. The sample size of this study was (n=120) and the data was cross-sectional in nature. The results reveal that the direct effect of agreeableness and distributive justice on organizational commitment is significant and positive while neuroticism has insignificant effect on organizational commitment. While the combined effect shows that both interactions terms has positive and significant effect on organizational commitment.